A Simple Tool for Solving Queuing Model with Erlang Distribution - Sakthi, R.; Vidhya, V.; Dhiki, T. (Asian Journal of Engineering and Applied Technology, 2015)
In this paper we use the online tool to find the performance measures of the steady-state behavior of the queuing model where inter arrival and service times are Erlang distributions with parameters k and m respectively. The suggested tool has a simple graphical interface, based on a recently published simple recurrence method[1], it provides the performance measures of the queuing system (i.e., average number in the system, average waiting time, the system utilization, probability of loss, probability of waiting time), also the steady-state distribution of the system.